Control of consistent ordering in π-conjugated polymer films for organic field-effect transistor applications. Issue 75 (26th July 2016) - Pei, Mingyuan; Park, Kwang Hun; Jang, Mi; Lee, Sang Bong; Ahn, Joongyu; Kim, Yun-Hi; Yang, Hoichang
Abstract : A conjugated copolymer, pDPP-(TV)2 B-2DO, including donor and acceptor blocks of 1, 4-bis(( E )-2-(thiophen-2-yl)vinyl)benzene and diketopyrrolopyrrole derivatives, respectively, was synthesized for organic field-effect transistor applications. Abstract : A novel conjugated copolymer, pDPP-(TV)2 B-2DO, including donor (D) and acceptor (A) blocks of (TV)2 B-2DO, 1, 4-bis(( E )-2-(thiophen-2-yl)vinyl)benzene with dodecyloxy moieties and diketopyrrolopyrrole (DPP) derivatives, respectively, was synthesized by Stille-coupling polymerization. The 60 kDa pDPP-(TV)2 B-2DO showed good solubility in organic solvents and strong molecular interaction during film procedures. Semiconducting thin films were spun-cast on polymer-treated SiO2 from chloroform and annealed at temperatures ranging from 150 to 300 °C for 1 h. The electrical properties of these films in organic field-effect transistors (OFETs) were evaluated and correlated with π-conjugated ordering of the pDPP-(TV)2 B-2DO, before and after annealing. Featureless aggregates of the face-on copolymer by the bulky B-2DO in the D block were dominant in the as-spun film and transformed into ordered rods or fibrils containing highly ordered edge-on polymers on the substrates after annealing. In terms of π-conjugated ordering, the as-spun and 250 °C-annealed pDPP-(TV)2 B-2DO films contained highly-consistent chains with face-on and edge-on structures, respectively. The resulting OFETs yielded similar field-effect mobilities of 0.07 and 0.08 cm 2 V −1 s −1, respectively, as well as on–off current ratios greater than 10 6 and a threshold voltage near 0 V. Therefore, the π-overlap of edge-on semiconducting polymers on gate dielectrics was not necessary to enhance the electrical performance of OFETs, but the high consistency in chain ordering was very important.